Truly Sustainable Responsibility : A New Research Direction Building on Environmental Management, Corporate Social Responsibility, and Corporate Sustainability (Editorial) - Kaivo-oja, Jari; Ainamo, Antti (MDPI, 2025)
The urgent need for accelerated deep transitions towards globally sustainable development pathways is now widely recognized. Research on responsible business has but begun to address this need. The three key research streams covered in this Special Issue are corporate sustainability (CS), corporate social responsibility (CSR), and environmental management (EM). We have highlighted that it is essential not only to examine CS, CSR, and EM as distinct research streams. We have instead mapped these three streams of research on responsible business as a dynamic, circularly operating and multilevel system framework [4], consisting of: (1) a global landscape, (2) national macro-level systems (socio-technical regimes), and (3) micro-level socio-cultural niche systems.
In this editorial, we illustrate how we see the five research articles in this special is them to synthesize into the emerging three-by-three, dynamic and global framework we call Truly Sustainable Responsibility (TSR). Also Geels [4] has highlighted the urgency of this kind of research. While the focal agency he has in mind is the National Academy of Sciences in the USA, this framework emphasizes the urgency of the need for transitions towards increasingly responsible and hopefully increasingly circular business models. Within the complex international supply chains of production and consumption by corporations and other players that characterize the modern economy, it is important to remember how the dynamics of the supply chains are embedded in an ecosystemic interplay of regulators, other public-policy actors, consumer-interest groups, and civil-society activists.
In this editorial, building upon the five articles within this Special Issue, as well as our review of EM, CSR, CS, and other sustainability-research literature, we thus propose our new concept and framework of TSR as a new research stream and set of new research directions, to both build on and to complement research still focused on CS, CSR, EM, or any combination thereof.
We believe that TSR research may most contribute to CS research. Tweaking CS research toward TS will extend CS research beyond current circular-economy analyses of costs and returns, to focus also on environmental impacts, such as on downcycling, on disposal, and on waste management. It may also extend CS research to consider creative, cultural and technological performance such as upcycling, smart products, and new materials. Promising research focused in one or several of the above ways has seminally already been carried out in industries such as the fashion industry, with commitment to clean up after deeds of also others than those one’s own, paying attention to upcycling [13], digitalization to increase the efficiency of information process [14], and data-sharing across corporations [15]. We foresee similar fruitful new research directions also in other industries. Advances in computer science and digitalization without a doubt will continue to enable rapid advances in EM, CSR, and CS. Multi-level empirical studies of enviro-socio-economic dynamics will produce ever new research-based knowledge in and across EM, CSR, and CS, as well as now also TSR, in and across industrial-corporate and governmental-policy players, consumers, as well as civil society pressure groups and activists.